The expression is equivalent to (f circle g) (x) will be (3x+2)²+1. The correct option is D.
A number is obtained by dividing another number by itself without leaving a leftover. To put it another way, if multiplying two whole numbers produces a product,
The given expression is;
[tex]f(x) = 3x + 2 \\\\ g(x) = x_2 + 1[/tex]
[tex](f g)(x) =g(f(x)) =g(3x+2)=(3x+2)^2 +1[/tex]
The expression is equivalent to (f circle g) (x) will be (3x+2)²+1. Option D is correct.
To learn more about the factors refer to the link;
brainly.com/question/24182713